174k views
4 votes
Given the second order homogeneous constant coefficient equation y′′−4y′−12y=0 1) the characteristic polynomial ar2+br+c is r^2-4r-12 . 2) The roots of auxiliary equation are (enter answers as a comma separated list). 3) A fundamental set of solutions is (enter answers as a comma separated list). 4) Given the initial conditions y(0)=1 and y′(0)=−26 find the unique solution to the IVP y= .

1 Answer

7 votes

Answer:

The initial value problem
y(x) = 4 e^(-2x) -3 e^(6 x)

Explanation:

Step1:-

a) Given second order homogenous constant co-efficient equation


y^(ll) - 4y^(l)-12y=0

Given equation in the operator form is
(D^(2) -4D-12)y=0

Step 2:-

b) Let f(D) =
(D^(2) -4D-12)y

Then the auxiliary equation is
(m^(2) -4m-12)=0

Find the factors of the auxiliary equation is


m^(2) -6m+2m-12=0

m(m-6) + 2(m-6) =0

m+2 =0 and m-6=0

m=-2 and m=6

The roots are real and different

The general solution
y = c_(1) e^{-m_(1) x} + c_(2) e^{m_(2) x}

the roots are
m_(1) = -2 and m_(2) = 6

The general solution of given differential equation is


y = c_(1) e^(-2x) + c_(2) e^(6 x)

Step 3:-

C) Given initial conditions are y(0) =1 and y1 (0) =-26

The general solution of given differential equation is


y(x) = c_(1) e^(-2x) + c_(2) e^(6 x) .....(1)

substitute x =0 and y(0) =1


y(0) = c_(1) e^(0) + c_(2) e^(0)


1 = c_(1) + c_(2) .........(2)

Differentiating equation (1) with respective to 'x'


y^l(x) = -2c_(1) e^(-2x) + 6c_(2) e^(6 x)

substitute x= o and y1 (0) =-26


-26 = -2c_(1) e^(0) + 6c_(2) e^(0)


-2c_(1) + 6c_(2) = -26 .............(3)

solving (2) and (3) by using substitution method


substitute c_(2) =1- c_(1) in equation (3)


-2c_(1) + 6(1-c_(1)) = -26

on simplification , we get


-2c_(1) + 6(1)-6c_(1)) = -26


-8c_(1) = -32

dividing by'8' we get
c_(1) =4

substitute
c_(1) =4 in equation
1 = c_(1) + c_(2)

so
c_(2) = 1-4 = -3

now substitute
c_(1) =4 and c_(2) =-3 in general solution


y(x) = c_(1) e^(-2x) + c_(2) e^(6 x)


y(x) = 4 e^(-2x) -3 e^(6 x)

now the initial value problem


y(x) = 4 e^(-2x) -3 e^(6 x)

User Urema
by
6.0k points